A hybrid model for biofilm growth on a deformable substratum. (19th March 2015) - Boraey, Mohammed A.; Guaily, Amr; Epstein, Marcelo
<x xml:space="preserve">Abstract</x> The mutual interaction between a biofilm growing on a deformable substratum and its deformability is investigated. The interaction process is investigated by a newly developed model based on a hybrid Cellular Automaton/Finite Element approach (CAFE). A quantitative model is proposed that predicts the effect of the substratum deformability on the biofilm growth as well as on the allocation of the newborn cells. In the proposed model, it is suggested that regions of higher positive curvature will act as attractors. The finite element method is used to model the substratum deformability while the biofilm growth is modelled using a semi‐stochastic approach. Numerical examples are presented in two‐ and three‐dimensional settings.